Isolation and Purification of Pyranose 2-Oxidase from Phanerochaete chrysosporium and Characterization of Gene Structure and Regulation - de Koker, Theodorus H. (American Society for Microbiology, 2004)
Pyranose 2-oxidase (POX) was recovered from Phanerochaete chrysosporium BKM-F-1767 solid substrate culture using mild extraction conditions and was purified. (13)C-nuclear magnetic resonance confirmed production of d-arabino-hexos-2-ulose (glucosone) from d-glucose with the oxidase. Peptide fingerprints generated by liquid chromatography-tandem mass spectrometry of tryptic digests and analysis of the corresponding cDNA revealed a structurally unusual sequence for the P. chrysosporium POX. Relatively high levels of pox transcript were detected under carbon-starved culture conditions but not under nutrient sufficiency. This regulation pattern is similar to that observed for lignin peroxidases, manganese peroxidases, and glyoxal oxidase of P. chrysosporium, supporting evidence that POX has a role in lignocellulose degradation.